Impedance Spectroscopy Analysis of the Effect of TiO2 Blocking Layers on the Efficiency of Dye Sensitized Solar Cells - Goes, Marcio Sousa [UNESP]; Joanni, Ednan; Muniz, Elaine C. [UNESP]; Savu, Raluca; Habeck, Thomas R. [UNESP]; Bueno, Paulo Roberto [UNESP]; Fabregat-Santiago, Francisco (Amer Chemical Soc, 2012)
The introduction of a dense TiO2 layer between the mesoporous TiO2 network and the charge collector in dye-sensitized solar cell anodes has been claimed to improve the performance of solar cell devices. Two mechanisms have been proposed to explain this behavior, a decrease in the electron-hole recombination at substrate/electrolyte interface and an enhancement in the electronic contact between the mesoporous TiO2 network and the charge collecting electrode. In this work the effect of sputtered TiO2 blocking layers (BLs) on the performance of dye-sensitized solar cells electrodes has been analyzed. It has been shown that the electron injection efficiency governed changes observed in cell efficiency. The thicker the BL, the poorer the photocurrent, and therefore, only thin BLs leaded to an increase in energy conversion efficiencies. The thickness of the BL also affected the internal series resistance of the solar cells, influencing their fill factor.